Angiotensin receptor-binding molecule in leukocytes in association with the systemic and leukocyte inflammatory profile. (February 2018) - Haruhara, Kotaro; Wakui, Hiromichi; Azushima, Kengo; Kurotaki, Daisuke; Kawase, Wataru; Uneda, Kazushi; Haku, Sona; Kobayashi, Ryu; Ohki, Kohji; Kinguchi, Sho; Ohsawa, Masato; Minegishi, Shintaro; et al.
Abstract: Background and aims: The components of the renin-angiotensin system in leukocytes is involved in the pathophysiology of non-communicable diseases (NCDs), including hypertension, atherosclerosis and chronic kidney disease. Angiotensin II type 1 receptor (AT1R)-associated protein (ATRAP) is an AT1R-specific binding protein, and is able to inhibit the pathological activation of AT1R signaling in certain animal models of NCDs. The aim of the present study was to investigate the expression and regulation of ATRAP in leukocytes. Methods: Human leukocyte ATRAP mRNA was measured with droplet digital polymerase chain reaction system, and analyzed in relation to the clinical variables. We also examined the leukocyte cytokines mRNA in bone-marrow ATRAP-deficient and wild-type chimeric mice after injection of low-dose lipopolysaccharide. Results: The ATRAP mRNA was abundantly expressed in leukocytes, predominantly granulocytes and monocytes, of healthy subjects. In 86 outpatients with NCDs, leukocyte ATRAP mRNA levels correlated positively with granulocyte and monocyte counts and serum C-reactive protein levels. These positive relationships remained significant even after adjustment. Furthermore, the leukocyte ATRAP mRNA was significantly associated with the interleukin-1β, tumor necrosis factor-α and monocyte chemotactic protein-1 mRNA levels in leukocytes of NCDs patients. In addition, the leukocyte interleukin-1β mRNA level was significantly upregulated in bone marrow ATRAP-deficient chimeric mice in comparison to wild-type chimeric mice after injection of lipopolysaccharide. Conclusions: These results suggest that leukocyte ATRAP is an emerging marker capable of reflecting the systemic and leukocyte inflammatory profile, and plays a role as an anti-inflammatory factor in the pathophysiology of NCDs. Highlights: ATRAP expressed in human leukocytes, predominantly granulocytes and monocytes. Leukocyte ATRAP mRNA correlated with the inflammation status in NCDs patients. Leukocyte IL-1β mRNA from BM-KO mice significantly enhanced after LPS injection. Leukocyte ATRAP may be a candidate marker reflecting the systemic and leukocyte inflammation.